Exploring changes in organizational purchasing behaviors brought about by COVID-19 as a catalyst for new directions in sales research. Issue 4 (7th December 2022) - Bonney, Leff; Beeler, Lisa; Chaker, Nawar N.
Abstract: The COVID-19 pandemic's disruption and ultimate lasting impact on the business world is unprecedented. While there has been much discussion about the specific impact that COVID-19 has had on salespeople and sales organizations as a whole, very little academic investigation has been focused on the impact of the pandemic in terms of the 'other side' of the buyer-salesperson dyad–namely, B2B buyers. This research aims to fill this void by providing initial insights into the changes that have emerged post COVID-19 in B2B buyer decision-making. Using qualitative interviews and an exploratory survey (with the goal of generalizing the initial findings across industries and contexts), our findings suggest that significant changes have emerged in the areas of (1) the organizational buying process, (2) how buyers source information, and (3) how buyers and salespeople interact. We expand on these core themes via a list of more detailed subthemes. The results serve as a catalyst for new and relevant avenues for sales related research regarding B2B in the new normal. Consequently, extensive future research directions are proposed.